Primipara Undergoing Episiotomy had Lower Postpartum Sexual Function - Irwan Irwan; Efendi Lukas; Nusratuddin Abdullah (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To compare postpartum sexual functions between primipara with episiotomy and without episiotomy. Method: The research was conducted in public service section of Dr. Wahidin Sudiro Husodo hospital and a number of educational hospitals obstetrics and gynecology of Faculty of Medicine of Hasanuddin University, started from February to May 2012. The research evaluated the sexual function of postpartum with episiotomy in 171 primipara, and 150 primipara postpartum without episiotomy. Sexual function was measured by Female Sexual Function Index (FSFI) questionnaire which had been validated in various countries. The research was conducted with cross sectional approach. Samples were withdrawn with consecutive sampling method. The data was processed with SPSS version 17, with chi-square test, and significant level of 0.05. Result: Indicated that either the episiotomy or non-episiotomy group has undisturbed sexual function score (>28.5), however, higher score was indicated in non-episiotomy group (65.477) compared to the episiotomy group (59.70), (p<0.05). Conclusion: Primipara with episiotomy and breastfeeding has lower sexual functions compared to the non-breastfeeding group, however, it was statistically insignificant (p>0.05). Keywords: episiotomy, FSFI, primipara, sexual functions